Aluminium to Carbon Fibre Reinforced Polymer tubes joints produced by magnetic pulse welding - Pereira, D. (2022)
Project SpIM, (2016/10605). ESA (ESA contract 4000111471/14/NL/PA). UID/EMS/00667/2019 (UNIDEMI).